Circular Business Models in Livestock Waste Management for Achieving Green Growth and Sustainable Agribusiness Development - Andi Nurmasytha; I Putu Gede Didik Widiarta; Khoiru Indana; Ardiansyah; Kirana Dara Dinanti Adiputra; Karenina Dwi Yulianti; Fadhil Muharram (Program Studi Magister Sains Pertanian Program Pascasarjana Universitas Warmadewa, 2025)
Sustainable agribusiness transformation in developing regions increasingly depends on adopting circular economy principles to optimize resource efficiency and minimize environmental impact. This study analyzes the implementation of Circular Business Models (CBMs) in livestock waste management as a foundation for achieving green growth and sustainable agribusiness development in Bukit Raya Village, Tenggarong Seberang District, Kutai Kartanegara Regency, East Kalimantan, Indonesia. A qualitative descriptive approach combined with a case study design was employed to examine the socio-economic, managerial, and environmental dimensions influencing CBM adoption among five farmer groups. Primary data were obtained through field observations, semi-structured interviews, and focus group discussions, while secondary data were sourced from institutional and academic reports. The results revealed that 76% of livestock waste, primarily goat and cattle manure, was successfully valorized into biogas and organic fertilizer, resulting in a 40% reduction in LPG use and a 17.7% increase in household income. Compost and biofertilizer commercialization integrated livestock systems into local agribusiness value chains, fostering market-based sustainability. Community-based innovation promoted inclusivity, with women and youth participation reaching 35% of total members. The conceptual framework developed from this study identifies four strategic pillars, resource efficiency, market-oriented integration, community-driven innovation, and institutional facilitation, as essential to transforming rural livestock systems toward a circular and regenerative agribusiness ecosystem. The findings underscore the importance of aligning rural development and policy interventions with circular economy principles to enhance environmental resilience and socio-economic equity within sustainable agricultural systems.